UTILIZATION ACTIVATED CHARCOAL OF HYACINTH AS PEAT WATER BIOFILTER USING ZnCl2 ACTIVATOR - Noor Khamidah; Hairu Suparto; Ita Oktavianingsih (Universitas Lambung Mangkurat, 2021)
Peat water is a type of water that does not meet the quality of clean water because it has a cloudy color, smells, tastes and low pH. One of the peat water repair technologies is to use activated charcoal to improve the quality of peat water. Water hyacinth has the potential to be used as activated charcoal because it has high levels of C-organic. Charcoal needs to be activated to open the pores, one of activator materials that can be used is ZnCl2. This study aims to determine the potential of water hyacinth activated charcoal to be used as a peat water biofilter, to determine the usefulness of ZnCl2 as a water hyacinth charcoal activator, and to determine the correct concentration of ZnCl2 activator for water hyacinth charcoal activation process. The research was conducted at the Production Laboratory of the Agroecotechnology Department, Animal Nutrition and Food Laboratory, Animal Husbandry Department, Agriculture Faculty, and Water Quality and Hydro-Bioecology Laboratory, Aquatic Resources Management Department, Fisheries and Marine Faculty, Lambung Mangkurat University, Banjarbaru, from December 2020-January 2021. This study used a completely randomly design (CRD) single factor that is difference in the concentration of ZnCl2 activator with 4 experimental units. Activated charcoal of water hyacinth can be used as a peat water biofilter as indicated by the parameters of turbidity, TDS, pH, temperature, taste and smells of water. ZnCl2 can be used as an activator for charcoal of water hyacinth using the physic-chemical activation method. The correct concentration of activator is ZnCl2 30%.